(untitled) (Experimental biology, 2015)
The results of the psikhrofilny petroleumoxidizing microorganisms identification are presented in this article. This microorganisms were allocated from territories of the West Kazakhstan , with the method of direct nucleotide sequence m 16 S RNA determination.